Cessation from Smoking Improves Innate Host Defense and Clearance of Experimentally Inoculated Nasal Staphylococcus aureus - Cole, Amy L.; Schmidt-Owens, Mary; Beavis, Ashley C.; Chong, Christine F.; Tarwater, Patrick M.; Schaus, James; Deichen, Michael G.; Cole, Alexander M. (Infection and immunity, 2018)
Staphylococcus aureus nasal carriage is transient in most humans and usually benign, but dissemination of S. aureus to extranasal sites causes the majority of clinical infections, and S. aureus is a major cause of serious infections in the United States. A better understanding of innate nasal decolonization mechanisms is urgently needed, as are relevant models for studying S. aureus clearance. Here, we screened a population of healthy smokers for nasal S. aureus carriage and compared the participants' abilities to clear experimentally applied nasal S. aureus before and after completion of a smoking cessation program. We determined that cigarette smoking increases the mean nasal S. aureus load (2.6 × 10 4 CFU/swab) compared to the load observed in healthy nonsmokers (1.7 × 10 3 CFU/swab) and might increase the rate of S. aureus nasal carriage in otherwise-healthy adults: 22 of 99 smokers carried S. aureus at the screening visit, while only 4 of 30 nonsmokers screened positive during the same time period. Only 6 of 19 experimental inoculation studies in active smokers resulted in S. aureus clearance within the month of follow-up, while in the cessation group, 6 of 9 subjects cleared nasal S. aureus and carriage duration averaged 21 ± 4 days. Smoking cessation associated with enhanced expression of S. aureus -associated interleukin-1β (IL-1β) and granulocyte colony-stimulating factor (G-CSF) in nasal fluids. Participants who failed to clear S. aureus exhibited a higher nasal S. aureus load and elevated nasal interleukin-1 receptor antagonist (IL-1RA) expression at the preexperiment study visits. We conclude that smokers exhibit higher S. aureus loads than nonsmokers and that innate immune pathways, including G-CSF expression and signaling through the IL-1 axis, are important mediators of nasal S. aureus clearance.